Coffee shop atmospheric effect on customer satisfaction and behavioural intention - Cut Aprilia; Ade Irma Suryani (BISMA (Bisnis dan Manajemen), 2020)
Despite the growing number of atmospheric studies in the various service settings such as restaurants and hotels, the application of atmospheric studies in the coffee shop has not gained much attention from scholars. The purpose of this study is to determine the coffee shop atmospheric dimension and the influence on customer satisfaction and behaviour intention of the coffee shop customers. The result of reviewing a large number of service environment literature has identified four dimensions of coffee shop atmospherics: facility aesthetic, ambience condition, spatial layout, and social. Subsequently, these dimensions are used to examine their role in customer satisfaction and behaviour intention. The data were collected from 298 coffee shop customers at ten coffee shops and each measurement was subjected for validity analysis of and composite reliability that were analyzed using confirmatory factor analysis (CFA). The relationship between variables was verified using the Structural Equation Model (SEM). The findings of this study are: first, the coffee shop atmospherics influence customer satisfaction positively; second, customer satisfaction has a mediation role in the relationship between coffee shop atmospheric and behaviour intention; third, customer satisfaction affects behaviour intention significantly. The findings implied that the coffee shop atmospheric has a paramount role in affecting customer satisfaction which can lead to positive behaviour intention of the customers such as spreading the positive word about the coffee shop and revisiting intention.